Effect of Fillial Value and Commitment To Family Ability in Early Detection of High Risk Pregnancy - Mardiyanti, Ika; Anggasari, Yasi (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Pregnancy and childbirth are physiological processes that women experience, but sometimes have risky conditions. This study aims to determine the effect of filial value and commitment to family ability in early detection of high risk pregnancy. This study used a cross sectional design. The sample size of 112 from a population of 155 by simple random sampling. Data analysis using SEM PLS. The results (52.7%) were in early adulthood , (62.5%) secondary education, (75%) worked in private (57.1%) had good self-esteem, (52, 7%) self -motivated enough, (50%) good previous behavior. SEM-PLS statistical analysis CFA, fillial value were 10.23 and commitment was 13.78, on family abilities. The value of the fillial value (0.201), the value of commitment (0.102). R2 value (0.63) and Q2 value of 0.65. In further research, it is necessary to involve other factors to increase family capacity, especially in the ability of families to detect high-risk pregnancies early.